A custom-made integrated system for thermoluminescence and radioluminescence spectroscopy - Nunes, Matheus C.S. [UNESP]; Rodrigues, Miguel L.; Silva, Walace J.R. [UNESP]; Silva, Ronaldo S.; Umisedo, Nancy K.; Yoshimura, Elisabeth M.; Trindade, Neilo M. (Elsevier, 2024)
Thermoluminescence (TL) and Radioluminescence (RL) are widely used in dosimetry applications. We present a custom-built integrated system, designated LUMI22, for measuring TL, TL spectroscopy, RL, and RL as a function of temperature. LUMI22 includes a heating system based on Kanthal® A1 alloy (FeCrAl), a microcontroller to regulate the temperature ramps (e.g. 1–5 °C/s). To irradiate samples an X-ray tube (Moxtek 50 kV, 50 μA) is powered, controlled, and monitored by an FTC-200 standard controller. The dose rate at the sample position is 0.43 Gy/min. Light collection includes a Photomultiplier Tube (PMT, Hamamatsu H10493-012:HA, 185–850 nm). Additionally, a miniature fiber optic spectrometer (Ocean Optics, QE65000, range 200–1100 nm) coupled with a 1000 μm diameter fiber optic (QP1000- 2-UV-VIS) was employed for TL and RL spectroscopy measurements. To assess the functionality of the system, it was used to measure TL and RL from Al2O3:C,Mg, Al2O3:C and TLD-100 phosphors which have been previously well investigated. The measured TL and RL data were well compared to the published ones, confirming the functionality of the system.
Keywords: Dosimetry; Radioluminescence; Scientific instrumentation; Spectroscopy TL; Thermoluminescence